Comparison of 24-h Urine Protein, Urine Albumin-to-Creatinine Ratio, and Protein-to-Creatinine Ratio in IgA Nephropathy - Yu, Guizhen; Cheng, Jun; Li, Heng; Li, Xiayu; Chen, Jianghua (Frontiers in Medicine, 2022)
Background. Proteinuria is a strong risk factor for renal outcomes in IgA nephropathy. Random urine protein-to-creatinine (PCR), random albumin-to-creatinine ratio (ACR) and 24-hour urine protein excretion (24-h UP) have been widely used in clinical practice. However, which measurement is the best predictor of long-term renal outcomes remains controversial. This study aimed to compare the three measurements in IgA nephropathy. Methods. We conducted a retrospective study of 766 patients with IgA nephropathy. The associations among baseline ACR, PCR and 24-h UP with CKD progression event, defined as 50% eGFR decline or ESKD, were tested and compared. Results. In this study, ACR, PCR and 24-h UP showed high correlation (r=0.671-0.847, P<0.001). After a median follow-up of 29.88 (14.65–51.65) months, 51 (6.66%) patients reached the CKD progression event. In univariate analysis, ACR performed better in predicting the prognosis of IgA nephropathy, with a higher area under the ROC curve than PCR and 24-h UP. After adjustment for traditional risk factors, ACR was most associated with composite CKD progression event (per log-transformed ACR, hazard ratio [HR], 2.82; 95% confidence interval [95% CI], 1.31-6.08; P=0.008). Conclusions. In IgA nephropathy, ACR, PCR and 24-h UP had high correlation. ACR performed better in predicting the prognosis of IgA nephropathy.